Mentalitas Peisan Melayu Jambi (Studi Kasus Sistem Mata Pencarian Hidup Peisan Melayu Desa Senaning Kabupaten Batanghari) - Pahmi, Pahmi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This article highlights the system of earning-living substances effort by Jambi-Malalt peasants employing cultural approach. From the way they are earning their living substances, it is revealed some of the prominent values they have in their daily life like in social contact, in religious ceremony and in economy. Desa Senaning is an example of how the people share their earning-living substances into each other, even though this sharing tends to be "to share the poverty". It is found that the way they earn their livelihood or necessities represents their very obvious mentality. In the other hand, they also tend to be commercialized and market oriented.